Vitamin D receptor expression is linked to potential markers of human thyroid papillary carcinoma. Issue 159 (May 2016) - Izkhakov, Elena; Somjen, Dalia; Sharon, Orli; Knoll, Esther; Aizic, Asaf; Fliss, Dan M.; Limor, Rona; Stern, Naftali
Highlights: ECM1, TMPRSS4 and VDR are highly expressed in papillary thyroid carcinoma. ECM1 expression is correlated with VDR expression in PTC patients. High Ca/N thyroid tissue mRNA ExR of VDR is linked to high ExR of ECM1 and/or TMPRSS4. Abstract: Genes regulated cell–cell and cell-matrix adhesion and degradation of the extracellular matrix (ECM) have been screened as potential markers of malignant thyroid nodules. The mRNA expression levels of two of them, the ECM protein-1 (ECM1) and the type II transmembrane serine protease-4 (TMPRSS4), were shown to be an independent predictor of an existing thyroid carcinoma. The vitamin D receptor (VDR) is expressed in epithelial cells of the normal thyroid gland, as well as in malignant dividing cells, which respond to the active metabolite of vitamin D by decreased proliferative activity in vitro . We evaluated the relationship between mRNA gene expressions of TMPRSS4, ECM1 and VDR in 21 papillary thyroid carcinoma samples and compared it to 21 normal thyroid tissues from the same patients. Gene expression was considered as up- or down-regulated if it varied by more or less than 2-fold in the cancer tissue relative to the normal thyroid tissue (Ca/N) from the same patient. We found an overall significant adjusted correlation between the mRNA expression ratio (ExR) of VDR and that of ECM1 in Ca/N thyroid tissue (R = 0.648, P  < 0.001). There was a high ExR of VDR between Ca/N thyroid tissue from the same patient (3.06 ± 2.9), which also exhibited a high Ca/N ExR of ECM1 and/or of TMPRSS4 (>2, P  = 0.05).The finding that increased VDR expression in human thyroid cancer cells is often linked to increased ECM1 and/or TPMRSS4 expression warrants further investigation into the potential role of vitamin D analogs in thyroid carcinoma.